From Sensibility to Performativity. Susan Sontag’s Theory of Camp, Revisited from a Hispanic Perspective - Ingenschay, Dieter (Estudios LGBTIQ+, Comunicación y Cultura, 2021)
Sontag’s concept of camp was a milestone for international cultural criticism. Her essay was also widely received in the Spanish-speaking world, above all by gay critics. Here, the reactions of two intellectuals who dealt with Sontag’s "Notes" early on are examined as examples: the Spanish Jaime Gil de Biedma, who relates the context of specific gay behavior in his country ("tener pluma") to Sontag’s theses, and the Mexican Carlos Monsiváis, who reflects on them in light of the historical and sociocultural situation of a Latin American country. Whereas these critics relate camp to the conditions in their own countries, the Argentine José Amícola interprets camp as an expression of international postmodernism. This is followed by the question of the role of the AIDS discussion and the relevance of "conscious camp" in the 21st century